Spectral estimation using digital filtering - Liu, Yongzhi. (2008)
In this work, the performance of the spectrum estimation using digital filters using various eigen-based methods, namely MUSIC, MN, UR are compared. Relationship between MN and UR are to be verified. And perturbation analysis pertain to UR is to be carried out.